Urridaholt neighbourhood Iceland - Sustainable drainage solutions interwoven in the urban pattern - a cooperative approach - Arnadottir, H.; Hreggvidsdottir, H. (HAL CCSD, 2016)
Colloque avec actes et comité de lecture. Internationale. International audience